IMPLEMENTASI HUKUM WARIS ISLAM PADA MASYARAKAT KECAMATAN KEPAHIANG KABUPATEN KEPAHIANG - Purbenazir, Eka Rahayu (UIN Fatmawati Sukarno Bengkulu, 2017)
This study raises the issue of implementation inheritance practices in society Kepahiang District of Kepahiang. So the urgency to fix the system of inheritance which has become a tradition for generations was considered good by most people Kepahiang to return it to the Islamic inheritance in order to create a qualified Muslim community. The purpose of this study (1) To investigate the implementation of the community Kepahiang inheritance; (2) To identify the background on which to base the distribution of the next of kin; (3) To analyze the views of Islamic law on inheritance practices implementation in society Kepahiang and add related intellectual treasures of Islamic heritage. This study uses content analysis (content analysis), with a historical-normative approach. The results showed that (1) In general practice division of the estate made by the people Kepahiang is with individual bilateral inheritance system through the deliberation and peace, this is done to anticipate disputes among heirs and to the achievement of welfare. It is also a habit of going on and practiced repeatedly and well-regarded in the community, while the comparison section received between heirs male and female heirs depending on the results of consultation with emphasis on the principle of mutual benefit and willingly accept any portion thereof, more often equally or 1:1; (2) The basis for the implementation of the division of inheritance in Kepahiang society is based on its own traditions that have been embraced for generations. Although there are based on the Islamic inheritance, only when executing by way of inheritance Islam, then the disagreement / dispute they choose to implement with the tradition that has been handed down it; (3) The distribution of inheritance in the District Kepahiang society Kepahiang using a system of equal division is not in accordance with Islamic law, because the procedure of distribution carried out by dividing the average whole inheritance to the heir on the legal basis is very weak. But the practice of the division of the estate in the District Kepahiang society can be viewed as the result of social construction, but in this Islamic regards the division of inheritance practices such as ‘urf fasid because it is contrary to the text (Nash) of syariat. Especially if the grounds of gender equality that will bring destruction and not in line with the objectives of the estabilishment of syari’at.